Atm heterozygosity does not increase tumor susceptibility to ionizing radiation alone or in a p53 heterozygous background - Mao, J H; Wu, D; DelRosario, R; Castellanos, A; Balmain, A; Perez-Losada, J (Oncogene, 2008)
Ataxia-Telangiectasia (A-T) is an autosomal recessive human disease characterized by genetic instability, radiosensitivity, immunodeficiency and cancer predisposition, because of mutation in both alleles of the ATM (ataxia-telangiectasia mutated) gene. The role of Atm heterozygosity in cancer susceptibility is controversial, in both human and mouse. Earlier studies identified deletions near the Atm gene on mouse chromosome 9 in radiation-induced lymphomas from p53 heterozygous mice. To determine whether Atm was the target of these deletions, Atm heterozygous as well as Atm/P53 double heterozygous mice were treated with ionizing radiation. There were no significant differences in tumor latency, progression and lifespan after γ-radiation in Atm heterozygous mice compared with their wild-type control counterparts. Deletions were found on chromosome 9 near the Atm locus in radiation-induced tumors, but in 50% of the cases the deletion included the knockout allele, and the expression of Atm was maintained in the tumors indicating that loss of heterozygosity on chromosome 9 is not driven by Atm , but by an alternative tumor suppressor gene located near Atm on this chromosome. We conclude that Atm heterozygosity does not confer an increase in tumor susceptibility in this context.